Implikasi Cryptocurrency Bitcoin Terhadap Konsistensi Regulasi Keuangan Dalam Perspektif Islam - Hanik Fitriani (LP3M STITNU Al Hikmah Mojokerto, 2018)
Along with the development of online transactions, helped change the payment method. Online transaction payments do not only use nominal amounts of money, but use a virtual money-shaped payment alternative called bitcoin. Bitcoin is one of the few digital currencies that originally appeared in 2009 which was introduced by Satoshi Nakamoto based on cryptography. Bitcoin uses peer-to-peer and open source technology. The appearance of bitcoin is considered to threaten the stability of financial regulation because Bank Indonesia has not regulated and made the policy of bitcoin movement. In addition, bitcoin also has some elements that are contrary to Islam so in practice bitcoin users should pay attention to several aspects. Bitcoin implications on financial regulation in Indonesia are the transactions that are conducted will lead to the potential of illegal transactions such as money laundering because it contains high speculation. In the absence of an authority that controls bitcoin, bitcoin users should be careful to avoid major losses. The government should immediately create a policy and legal umbrella so that bitcoin users are not harmed. Shari'a mad bitcoin bit is greater than its first since the first, bitcoin has a volatile value. Second: Contains element of speculation, third: money must have underlaying assets to serve as the basis of the transaction, fourth: big systemic risk.